Manet and modern beauty : the artist's last years - Allan, Scott; Alsdorf, Bridget; Armstrong, Carol M.; Beeny, Emily A.; Burnham, Helen; Groom, Gloria Lynn; Lehmbeck, Leah; Ormond, Devi; Art Institute of Chicago; J. Paul Getty Museum (The J. Paul Getty Museum, 2019)
"An examination of the last years of the artist Édouard Manet's life and work" Provided by publisher
Keywords: Manet, Édouard, : 1832-1883 : Exhibitions; Manet, Édouard, : 1832-1883 : Criticism and interpretation; 1800-luku; 1800-talet; bildkonstnärer; konstutställningar; maalaustaide; målarkonst; taidemaalarit; taidenäyttelyt; Frankrike; Ranska